Options for aerial surveys of elephants - G. Craig (Pachyderm)
In most areas where elephants occur, aerial surveys are the only means used to establish their numbers. The most common methodology is the systematic reconnaissance flight or the transect sample count, which, however, has been criticised as being inadequate. Other methods to supplement the standard methodology are reviewed.